Advanced Maternal Age in IVF: Still a Challenge? The Present and the Future of Its Treatment - Ubaldi, Filippo Maria; Cimadomo, Danilo; Vaiarelli, Alberto; Fabozzi, Gemma; Venturella, Roberta; Maggiulli, Roberta; Mazzilli, Rossella; Ferrero, Susanna; Palagiano, Antonio; Rienzi, Laura (Frontiers in endocrinology (Lausanne), 2019)
Advanced maternal age (AMA; >35 year) is associated with a decline in both ovarian reserve and oocyte competence. At present, no remedies are available to counteract the aging-related fertility decay, however different therapeutic approaches can be offered to women older than 35 year undergoing IVF. This review summarizes the main current strategies proposed for the treatment of AMA: (i) oocyte cryopreservation to conduct fertility preservation for medical reasons or "social freezing" for non-medical reasons, (ii) personalized controlled ovarian stimulation to maximize the exploitation of the ovarian reserve in each patient, (iii) enhancement of embryo selection via blastocyst-stage preimplantation genetic testing for aneuploidies and frozen single embryo transfer, or (iv) oocyte donation in case of minimal/null residual chance of pregnancy. Future strategies and tools are in the pipeline that might minimize the risks of AMA through non-invasive approaches for embryo selection (e.g., molecular analyses of leftover products of IVF, such as spent culture media). These are yet challenging but potentially ground-breaking perspectives promising a lower clinical workload with a higher cost-effectiveness. We also reviewed emerging experimental therapeutic approaches to attempt at restoring maternal reproductive potential, e.g., spindle-chromosomal complex, pronuclear or mitochondrial transfer, and chromosome therapy. generation of gametes is also an intriguing challenge for the future. Lastly, since infertility is a social issue, social campaigns, and education among future generations are desirable to promote the awareness of the impact of age and lifestyle habits upon fertility. This should be a duty of the clinical operators in this field.